Leadership and Motivation to Performance through Job Satisfaction of Hotel Employees at D'Merlion Batam - Yandra Rivaldo (The Winners, 2021)
The research aimed to confirm the theory with empirical evidence focusing on leadership, employee motivation, employee job satisfaction, and employee performance. The research applied a causal model survey method with path analysis techniques. The population were 45 employees of the D'Merlion Hotel Batam, and the sample was taken by using a census method. The significance value of leadership on job satisfaction is 0,082 > 0,05, it is concluded that direct leadership has no significant effect on job satisfaction. The significance value of motivation on job satisfaction is 0,000 < 0,05, which implies that motivation has a significant direct effect on job satisfaction. With similar significance value of 0,000 < 0,05, leadership has a significant direct effect on employee performance. Motivation has a significant direct effect on employee performance with significance value of 0,009 < 0,05. Lastly, with the significance value of 0,008 < 0,05, job satisfaction directly has a significant effect on employee performance.